Effect of Sonication Frequency and Power Intensity on the Disruption of Algal Cells: Under Vacuum and Non-Vacuum Conditions - Martin Darmasetiawan; Prayatni Soewondo; Suprihanto Notodarmodjo; Dion Awfa (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
The presence of algae caused by anthropogenic eutrophication in water has become a severe environmental issue. Various treatment options for algae removal have been developed, such as filtration, coagulation, sedimentation, flotation, algicides, ozone, and photolysis. However, these technologies are complex, expensive, consume considerable amounts of various chemicals, and may cause further pollution (i.e., by-product formation). Ultrasonic exposure is an alternative method for removing algae from water that is environmentally friendly (i.e., no addition of chemicals) and almost unaffected by any turbidity in the water. In this study, process optimization of ultrasonication (e.g., by adjusting frequency, power intensity, and exposure time) for the removal of alga was tested under vacuum and non-vacuum conditions. Experiments were conducted on a batch of algae solution in a clear glass tube ultrasonicated by a 20 kHz transducer for 180 minutes. The tube was depressurized up to -67 N/m2 in a depressurizing chamber. The data was collected at transducer depths of 0.06, 0.13, and 0.19 m. It was concluded that the optimum condition (i.e., 92% algal cell disruption) was achieved when the power intensity was 7 kWh/m3, under vacuum conditions, at a frequency of 20 kHz and 180 minutes of exposure time. Higher power intensity gave higher energy for cell disruption, moreover by depressurizing the air above the algae solution, the lysis effect for algae reduction increased from 20% to 70% compared to the non-depressurized system due to higher cavitation bubble production. In addition, the depth of the transducer was another factor that could increase the lysis of the algae water. Therefore, this technology has future potential application for algae removal from water.